Visualizing Evaluation Theory: Tree, Forest, or Ocean Currents? - Donna Mertens (The Evaluation Center at Western Michigan University, 2024)
Evaluation theories depicted as a five-branch tree reflect the assumptions of the post-positivist, constructivist, pragmatic, transformative, and Indigenous paradigms. A tree is useful because it provides a quick and clear way to show that different assumptions lead to different methodological assumptions. However, evaluation theory as a five-branch tree is limited because it does not show interrelationships between the paradigms. An ocean current visualization could accomplish that task, but it might not be a familiar concept for some populations. Evaluators need to check with stakeholders to ensure the visualizations that are used are viewed as useful to their purposes.